ANALISIS GEOTEKNIK DITINJAU DARI KARAKTERISTIK KUAT GESER MATERIAL LONGSORAN PADA BATAS KOTA JAYAPURA KABUPATEN KEEROM-ARSO STA. 66+327) - Edoward JP Pardede; Duha Awaluddin; T Bernathius (UKI Press, 2023)
Landslides Geotechnical analysis of the shear strength characteristics of landslide material on the Trans Papua national road, Arso-waris Yetti KM.66+327 segment, soil physical properties test based on laboratory test results on landslide material obtained at a depth of 1.00 m to 1.50 m is the water content. Original average: 21.25, specific gravity: 2.68, liquid limit (LL): 38.3, plastic limit (PL): 26.41, plastic index (PI): 11.89, soil type: clay sand silt, test The following laboratory mechanical properties were obtained: friction angle (): 14.00°, cohesion (c): 0.018 kg/cm, and wet bulk weight (s): 1.97 gr/cc. For unconfined compression tests, shear strength (qu) is 0.009 kg/cm2, depth 5.00 m to 6.0 m is the average original water content of 24.0, specific gravity 2.62, Limit liquid (LL) 36.6, plastic limit (PL) 18.10, plastic index (PI) 18.50. The type of soil detected is clay sand silt, laboratory mechanical properties tests were achieved for shear angle (Ø): 12.12°, cohesion (c) is 0.014 kg/cm, and wet bulk weight (s) is 1.88 gr/cc. The dry bulk weight (d) is 1.52gr/cc, the unconfined compression test shear strength (qu) is 0.0071 kg/cm2, the depth is 13 m to 14 m, the original water content is an average of 27.05, the specific gravity is 2.71, the liquid limit (LL) is 29.0, the plastic limit (PL) is 12.80, and the plastic index (PI) is 16.20. The soil type detected was shale, clay sand, and laboratory mechanical properties tests revealed shear angle (): 21.59°, cohesiveness (c): 0.025 kg/cm, and wet bulk weight (s): 2.09 gr/cc. The dry weight (d) is 1.64 gr/cc, and the shear strength of the free compression test (qu) is 0.0127 kg/cm2.